Digital collage with Procreate create beautiful mixed-media art on your iPad - Fitz-Gerald, Nicki (Rocky Nook, 2024)
Digital Collage with Procreate is the ultimate guide to every step of creating beautiful, one-of-a-kind mixed media artwork. Using the versatile and intuitive iPad drawing and design app Procreate, author and artist Nicki Fitz-Gerald composes a series of fun and easy projects that will build confidence by giving all the necessary tools to create gorgeous compositions from scratch.
Keywords: Procreate (Application software); Collage; Mixed media (Art); iPad (Computer); Computer art; Collage (Art); Technique mixte (Art); iPad (Ordinateur); collage (technique); mixed media